Strategic management of business-critical information assets - Bedford, Denise A. D., 1990- (Business Science Reference, 2019)
"This book examines the challenges and opportunities of managing information as a capital asset. It explores how to develop an effective information asset management strategy and how to operationalize and sustain that strategy through governance"--